Mekanisme Penyelesaian Sengketa Debitur Ingkar Janji oleh BPSK Samarinda dalam Perspektif Perlindungan Konsumen - Feby Soviani Stiawati; Wahyuni Safitri (International Journal of Politic, Public Policy and Environmental Issues, 2024)
Consumer disputes between defaulting bank debtors and banks are a crucial issue in consumer protection within the financial services sector. This research aims to examine the efforts and obstacles faced by the Consumer Dispute Settlement Board (BPSK) of Samarinda City in resolving such disputes, viewed through Law No. 8 of 1999 concerning Consumer Protection. Employing a normative juridical research method supplemented by interview data, this study analyzes BPSK's authority, procedures, and challenges. The findings indicate that BPSK Samarinda endeavors to resolve these disputes, particularly through mediation. BPSK facilitates dialogue between consumers (debtors) and business actors (banks), provides education, and guides the parties toward achieving amicable, win-win solution agreements according to established procedures. However, BPSK encounters significant constraints, including potential jurisdictional overlap with other financial sector dispute resolution bodies (LAPS-SJK), limitations in the legal basis specifically governing its authority in the banking sector, late reporting by consumers after enforcement actions (auctions), and insufficient public awareness, sometimes coupled with delayed responsiveness from business actors. Although BPSK serves as an accessible and low-cost alternative dispute resolution mechanism, strengthening its legal foundation and conducting massive outreach are necessary to enhance its effectiveness in handling complex banking disputes.